Properties of compression moulding starch - nanoclay biocomposites - Ahmad, Zuraida; Anuar, Hazleen (2011)
Most of the thermoplastic starch (TPS) is prepared via extruding machine and hot pressing method. The traditional thermoplastic starch was plasticized by water. This blend however, produces a brittle and lower strength of samples [1]. Glycerol and acylamide were among the plasticizers used to improve the strength of TPS. The presences of the inorganic-nano materials were among the routes to improve some of the properties of biodegradable polymers. The nano-composites obtained by the addition of low percentages of clay to polymers exhibited and improvement in the properties such as strength, thermal and oxidative when compared with traditional composites. Clay minerals are aluminum silicates of a layered type classified as phyllosilicates [2,3].